Acompanhamento Farmacoterapêutico em paciente idoso e polifarmácia: um relato de caso - de Matos, Ketlen Martins; Nascimento, Juliana Couto; de Matos, Paola Martins; de Andrade, Renata Aline (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
Aging is responsible for the increase in Chronic Noncommunicable Diseases and, as a result, a greater portion of the elderly population adopts the use of multiple medications as treatment. Pharmacotherapeutic monitoring becomes necessary to solve problems related to the use of multiple medications. The objective of this study is to present the pharmacotherapeutic monitoring of an elderly person on polymedication assisted by a School Pharmacy. The study uses a qualitative and descriptive case report methodology, adapted from the Dáder Method, and is conducted in three pharmaceutical consultations during the period from April to June 2024 in Diamantina. The first consultation consisted of collecting personal and clinical data followed by a demonstration of inhalation technique. The second consultation fully investigated drug overdose and dosage adjustments. The third consultation detected problems with self-medication and lack of adherence to the specific and complete medication in the organizer box. Pharmaceutical guidance is essential for self-management of health and the rational use of medications to avoid adverse effects. The pharmaceutical care disciplines proposed throughout the work in relation to pharmacotherapy were accepted by the elderly and there was an improvement in the patient’s quality of life.